2018
DOI: 10.5194/bg-15-1879-2018
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial biomass, activity and community composition along altitudinal gradients in the High Arctic (Billefjorden, Svalbard)

Abstract: Abstract. The unique and fragile High Arctic ecosystems are vulnerable to global climate warming. The elucidation of factors driving microbial distribution and activity in arctic soils is essential for a comprehensive understanding of ecosystem functioning and its response to environmental change. The goals of this study were to investigate microbial biomass and activity, microbial community structure (MCS), and their environmental controls in soils along three elevational transects in the coastal mountains of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 84 publications
(72 reference statements)
0
19
1
Order By: Relevance
“…Phospholipids were eluted with 2 cm 3 methanol and subjected to mild alkaline metanolysis according to Dowling et al (1986) and Oravecz et al (2004). Samples were analyzed on an Agilent Trace 1310 GC (Agilent, Wilmington, Delaware, USA) equipped with a flame ionization detector and a 60 m × 0.32 mm BPX70 × 0.25 μm column (SGE Analytical Science) (Kotas et al, 2018). The results were processed using Chromeleon 7.2.…”
Section: Microbial Analysesmentioning
confidence: 99%
“…Phospholipids were eluted with 2 cm 3 methanol and subjected to mild alkaline metanolysis according to Dowling et al (1986) and Oravecz et al (2004). Samples were analyzed on an Agilent Trace 1310 GC (Agilent, Wilmington, Delaware, USA) equipped with a flame ionization detector and a 60 m × 0.32 mm BPX70 × 0.25 μm column (SGE Analytical Science) (Kotas et al, 2018). The results were processed using Chromeleon 7.2.…”
Section: Microbial Analysesmentioning
confidence: 99%
“…Similar inconsistencies with altitude were found in microbial communities. Kotas et al (2017) showed that in the Arctic, microbial biomass increases with altitude, but it seems that such responses may be taxon dependent (Gremmen et al 2007;Bryant et al 2008).…”
Section: Altitude and Moisturementioning
confidence: 99%
“…Although altitude may not have a direct impact on soil organic matter (SOM) turnover, it can still influence this process indirectly by shaping soil, climatic, and vegetation conditions (Sierra and Causeret, 2018;Devi and Sherpa, 2019). Climatic conditions (i.e., decreased temperature and humidity) are heavily influenced by altitude, which in turn affects vegetation distribution/composition and alters the quality and quantity of litter/soil characteristics and C loss (Kotas et al, 2018;Quan et al, 2019). Recent studies have documented how changes in climatic conditions and forest canopy composition associated with altitude can affect the litter decomposition rate (Cardelli et al, 2019), soil microbial/enzyme activities (Feng et al, 2019;D'Alò et al, 2021), and nutrient storage in different ways (Bello et al, 2015).…”
Section: Introductionmentioning
confidence: 99%